Legislative and jurisprudential considerations regarding the regulation of online pharmacies - Erimia, Cristina-Luiza; Dumitrescu, Denisa-Elena; Schröder, Verginica; Cazacincu, Radu-George; Roncea, Florentina-Nicoleta (Technium BioChemMed, 2023)
As a result of the evolution of information and communication technologies, medicines, like other goods, are now increasingly marketed on the EU internal market through these channels. When examining the compatibility of the conditions for the supply of retail medicinal products with European Union law, the Court of Justice has recognized the specific nature of medicinal products, whose therapeutic effect significantly distinguishes them from other goods. Taking into account all these aspects, this article aims to analyse the centralized regulation of online pharmacies in relation to European Union law, the jurisprudence of the Court of Justice of the European Union, as well as the legislative measures taken at national level to provide medicinal products to the population through the Internet.